Implante Contraceptivo Não Palpável - Estratégias para a sua Localização e Remoção - Isidro Amaral, P (2013)
Overview and Aims: The contraceptive implant is frequently used to provide contraceptive protection over three years. The implant is inserted into the subcutaneous tissue of the upper arm, and should be palpable and easily removed. We evaluated the best imaging strategy for non-palpable implant (Implanon®) localization and removal. Study Design: Retrospective study. Population: A total of 11 women referred to a tertiary care hospital, between October 2009 and January 2012, for localization and removal of their non-palpable implants. Methods: Different localization methods (ultrasound and magnetic resonance imaging) were evaluated for non-palpable rod. Results: Seven of the nonpalpable implants were inserted in a health care center, three in a district hospital and one in a private clinic. In three women, the reasons for requesting removal were the end of the implant validity, two wanted to become pregnant, two had weight gain, one had weight loss, one referred irregular bleeding, one had two implants and one did a hysterectomy. In 81.8% (9) of the women, the implants were identified and localized by ultrasound, and successfully removed. In two patients the implant was not found and therefore not removed. Conclusions: In our study, high resolution ultrasound proved to be a sensitive method in implants localization, being the primary choice for determining the location of nonpalpable implants.